Infection surveillance in nursing homes in Stockholm County, Sweden, 2005 - 2014 - Tammelin, Ann (International Journal of Infection Control, 2016)
Swedish nursing homes are obliged to have a management system for systematic quality work including self-monitoring of which surveillance of infections is one part. The Department of Infection Control in Stockholm County Council has provided a simple system for infection surveillance to the nursing homes in Stockholm County since 2002. A form is filled in by registered nurses in the nursing homes at each episode of infection among the residents. A bacterial infection is defined by antibiotic prescribing and a viral infection by clinical signs and symptoms. Yearly reports of numbers of infections in each nursing home and calculated normalized figures for incidence, i.e. infections per 100 residents per year, as well as proportion of residents with urinary catheter are delivered to the medically responsible nurses in each municipality by the Department of Infection Control. Number of included residents has varied from 4,531 in 2005 to 8,157 in 2014 with a peak of 10,051 in 2009. The yearly incidences during 2005 - 2014 (cases per 100 residents) were: Urinary tract infection (UTI) 7.9-16.0, Pneumonia 3.7-5.3, Infection of chronic ulcer 3.4–6.8, Other infection in skin or soft tissue 1.4–2.9, Clostridium difficile-infection 0.2–0.7, Influenza 0–0.4 and Viral gastroenteritis 1.2–3.7. About 1 % of the residents have a suprapubic urinary catheter, 6–7 % have an indwelling urinary catheter. Knowledge about the incidence of UTI has contributed to the decrease of this infection both in residents with and without urinary catheter.